Salivary Gland Extract Modulates the Infection of Two Leishmania enriettii Strains by Interfering With Macrophage Differentiation in the Model of Cavia porcellus - Pinheiro, Lucélia J.; Paranaíba, Larissa F.; Alves, Adriano F.; Parreiras, Patrícia M.; Gontijo, Nelder F.; Soares, Rodrigo P.; Tafuri, Wagner L. (Frontiers in Microbiology, 2018)
The Subgenus Mundinia include several Leishmania species that have human and veterinary importance. One of those members, Leishmania Mundinia enriettii was isolated from the guinea pig Cavia porcellus in the 1940s. Several histopathological studies have already been performed in this species in the absence of salivary gland extract (SGE), which are determinant and the early and future events of the infection. Our main hypothesis is that SGE could differentially modulate the course of the lesion and macrophage differentiation caused by avirulent and virulent L. enriettii strains. Here, the C. porcellus nasal region was infected using needle with two strains of L. enriettii (L88 and Cobaia) in the presence/absence of SGE and were followed for 12 weeks. Those strains vary in terms of virulence and their histopathological development was characterized. Some L88-infected animals could develop ulcerated/nodular lesions, whereas Cobaia strain developed non-ulcerated nodular lesions. Animals experimentally inoculated developed a protuberance and/or lesion after the 4th and 5th week of infection. Macroscopically, the size of lesion in L88-infected animals was smaller in the presence of SGE. Remarkable differences were detected microscopically in the presence of SGE for both strains. After 6th and 7th weeks, L88-infected animals were heavily parasitized with an intense inflammatory profile bearing amastigotes and pro-inflammatory cells compared to those infected by Cobaia strain. Morphometry analysis revealed that L1+ macrophages were abundant in the L88 infection, but not in the Cobaia infection. In the presence of SGE, an increased CD163+ macrophage infiltrate by both strains was detected. Interestingly, this effect was more pronounced in Cobaia-infected animals. This study showed the role of SGE during the course of L. enriettii (strains L88 and Cobaia) infection and its role in modulating macrophage attraction to the lesion site. SGE decreased L1+ macrophages and this may favor an escaping mechanism for L88 parasites. On the other hand, in the presence of SGE, an increase in CD163+ cells during Cobaia infection may be important for its control. Although both strains healed at the end of the infection, the role of SGE was determinant for the kinetics of the immunopathological events in this dermotropic species.